A case of cerebral phaeohyphomycosis caused by Fonsecaea monophora, a neurotropic dematiaceous fungus, and a review of the literature. Issue 3 (15th January 2015) - Doymaz, Mehmet Z.; Seyithanoglu, Mehmet F.; Hakyemez, İsmail; Gultepe, Bilge S.; Cevik, Serdar; Aslan, Turan
Summary The Fonsecaea species, which are the leading causes of chromoblastomycosis, are not considered neurotropic fungal agents. Fonsecaea pedrosoi is the primary species in the genus and is usually isolated from chromoblastomycosis cases. However, the recently distinguished species F. monophora has been reported in a few cerebral phaeohyphomycosis cases. Here, a case of cerebral phaeohyphomycosis caused by Fonsecaea monophora is presented in a 71‐year‐old female subject with chronic diabetes mellitus and hypertension. The identification of F. monophora was made through mycological and molecular analysis, and an isolate was differentiated from the closely related F. pedrosoi by sequence data on key bases on the ribosomal internal transcribed spacer region. The case was successfully treated with surgical and medical approaches, and the patient has remained healthy and stable after a ten‐month follow up. Given the increasing incidence of this type of infection of the central nervous system (CNS), this case provides further support for the consideration that F. monophora might represent a neurotropic agent.